Implementação das tecnologias educacionais na rede municipal de ensino de Santa Maria: desafios da continuidade - Neocatto, Maritê Medianeira Moro (2018)
The present research, elaborated in the research line of Management in Educational Technologies in Network and in the Area of Concentration Educational Technologies in Network for Innovation and Democratization of Education in the Course of Professional Masters in Educational Technologies in Network, of UFSM, brought as a theme the implementation of the educational technologies in the Santa Maria Municipal Education Network, provided by PROINFO - National Program of Informatics in Education and, consequently, the role of the Municipal Educational Technology Center - NTEM. The research had as a guiding question, to analyze what were the possible advances and weaknesses potentiated by PROINFO regarding the use of educational technologies in municipal public schools and the role of NTEM as part of the operational structure of PROINFO in the municipality. To do so, it is necessary to: Map the possible advances and weaknesses potentialized by the implantation of PROINFO in the municipal network of Teaching of Santa Maria, starting from the vision of the teachers who were crowded like teachers multipliers of the NTEM of Santa Maria; To analyze how the Educational Technologies are being used in the schools and their integration with the pedagogical practice of the teachers, considering the role of the NTEM as a training center; To investigate if the Political-Pedagogical Projects of the schools contemplate the use of technologies and signal the creation of a Bill that disposes on the Nucleus of Municipal Educational Technology, like a Permanent Public Policy of the Municipality of Santa Maria. For the accomplishment of this research, the methodology of the case study was used. In the exploratory phase, the initial design was carried out with a survey of municipal schools, the public school system with computer rooms from PROINFO, the search for publications on the subject, documentary research at NTEM and SMED, among others. In the data collection phase, questionnaires and interviews were prepared and sent online to the 50 schools with computer rooms and to the teachers who were and are part of the NTEM team. The data analysis phase, the last phase of the study, was aimed at categorizing and classifying them, taking into account the initial propositions of the study. The evidence indicates that the insertion of technologies in Santa Maria municipal public schools, initiated by PROINFO's public policy, must transcend political mandates. It is necessary that the municipality has its public policy for the technologies, strengthening NTEM as the body that manages this policy: gestating, executing, monitoring and evaluating all activities, projects and programs, in short, all actions related to the use of technologies in n schools of the Network municipal of Santa Maria. As a final product, the documentation of the NTEM: PPP and regiment was updated, as well as the proposal for a regulation laying downon the NTEM as a permanent Public Policy in the Municipality of Santa Maria.